2012
DOI: 10.1182/blood-2011-08-375303
|View full text |Cite
|
Sign up to set email alerts
|

Heme induces programmed necrosis on macrophages through autocrine TNF and ROS production

Abstract: Diseases that cause hemolysis or myonecrosis lead to the leakage of large amounts of heme proteins. Free heme has proinflammatory and cytotoxic effects. Heme induces TLR4-dependent production of tumor necrosis factor (TNF), whereas heme cytotoxicity has been attributed to its ability to intercalate into cell membranes and cause oxidative stress. We show that heme caused early macrophage death characterized by the loss of plasma membrane integrity and morphologic features resembling necrosis. Heme-induced cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
176
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(197 citation statements)
references
References 52 publications
(105 reference statements)
10
176
4
Order By: Relevance
“…Mø also undergo programmed cell death when exposed to labile heme [58]. However, labile heme induces Mø to undergo necroptosis, rather than apoptosis.…”
Section: Labile Heme As a Cytotoxic Agonistmentioning
confidence: 99%
“…Mø also undergo programmed cell death when exposed to labile heme [58]. However, labile heme induces Mø to undergo necroptosis, rather than apoptosis.…”
Section: Labile Heme As a Cytotoxic Agonistmentioning
confidence: 99%
“…In addition, activation of TLRs and downstream inflammatory signaling, particularly of the TLR-4 pathway, can be triggered by free hemin in some models. [22][23][24] In summary, the definitive pathophysiology of extracellular Hb is dependent on timing, quantity, and tissue localization of Hb/ hemin exposure in a specific clinical condition and may result from cumulative effects largely described by the 4 mechanisms discussed in the sections above. For example, systemic and, to some extent, pulmonary hypertension is the most apparent and readily measurable effect of free Hb after intravascular hemolysis.…”
Section: Mechanism 2: No and Oxidant Reactionsmentioning
confidence: 99%
“…Whereas heme-induced TNF production depends on functional toll-like receptor 4 (TLR4), ROS generation in response to heme is TLR4 independent (19). We recently observed that heme triggers receptor-interacting protein (RIP)1/3-dependent macrophage-programmed necrosis through the induction of TNF and ROS (15). The highly unstable nature of iron is considered critical for the ability of heme to generate ROS and to cause inflammation.…”
mentioning
confidence: 99%
“…Blocking the prooxidant effects of heme protects cells from death and prevents tissue damage and lethality in models of malaria and sepsis (12,13,15). Importantly, two recent studies demonstrated the pathogenic role of heme-induced TLR4 activation in a mouse model of sickle cell disease (29,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation